Impact Analysis of the Implementation of Law No.16 of 1964 concerning Fishermen's Profit Sharing in Gebang District Cirebon Regency - Faldi, Tri (Ann Publisher, 2023)
Fisheries product sharing agreements are recognized by positive law in Indonesia, which is governed by Law Number 16 of 1964 Governing Fisheries Product Sharing. In reality, the law is ineffective because the fishing community in Gebang District, Cirebon Regency, continues to conduct its business as usual. Observation, interviews, and literature study are the three methods employed in the juridical-empirical technique, which uses two categories of legal resources: primary and secondary legal materials. With the help of this study, fishing communities in Gebang District, Cirebon Regency, would be able to share fisheries products in accordance with the law. According to the study's findings, regulations that aim to empower fishermen through initiatives like business-verified mentoring, cooperative procurement, and auctions incorporate the legal components of sharing fishery products. Law Number 16 of 1964, which also governs fundamental issues like the quantity of product sharing to which fishermen are entitled, regulates product sharing in the fishing industry. For this reason, it is advised that local governments be more proactive in performing monitoring and control so that the enforcement and implementation of rules and regulations can proceed as they should. This includes bringing legal aspects of the sharing of fishery products closer to the community.